Diagnosis and surgical therapy of the retroperitoneal ectopic pregnancy: A case report. (2018) - Yang, Yizhuo; Liu, Zhongyu; Song, Lei; Liu, Hui; Li, Lian; Meng, Yuanguang
Highlights: A rare case of retroperitoneal ectopic pregnancy received surgical treatment was reported. Discuss the mechanisms of retroperitoneal embryo migration. Review related literatures of retroperitoneal embryo migration and discuss the surgical method. Abstract: Introduction: Retroperitoneal ectopic pregnancy (REP) is a rare type of gestation that is difficult to diagnose and treat. To date, only several published cases are available and no specific guideline has been developed to manage this disease. As the lesions are located closely to the large retroperitoneal blood vessels, surgical resection of the gestational tissue might incur risks such as associated hemorrhage, injury of blood vessels or nerves. On the other hand, the therapeutic effect of conservative treatment using methotrexate is not satisfactory. Presentation of case: A case of retroperitoneal ectopic pregnancy which was diagnosed in the PLA general hospital was reported here. A 34-year-old woman, gravida 2, parturition 0, was admitted via the emergency department on July 7, 2015 with the main complaint of missed period for 52 days and bellyache for 16 h. Discussion: The mechanisms of retroperitoneal embryo migration and related literatures are reviewed and discussed. Conclusion: We have presented a scarce case of REP. As the ectopic pregnancy could not be readily detected by laparotomy, unusual locations such as the retroperitoneum should be carefully examined.